2002
DOI: 10.1038/sj.onc.1205888
|View full text |Cite
|
Sign up to set email alerts
|

BTG2TIS21/PC3 induces neuronal differentiation and prevents apoptosis of terminally differentiated PC12 cells

Abstract: The p53-transcriptional target, BTG2 TIS21/PC3 , was previously identified as an antiproliferative gene. However, the precise biological functions of the protein product remain to be elucidated. BTG2 TIS21/PC3 expression is induced in vivo during neurogenesis, and the gene is transiently expressed in vitro in rat pheochromocytoma PC12 cells after induction of neuronal differentiation by addition of nerve growth factor (NGF). These observations suggest that BTG2 TIS21/PC3 is functionally significant during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 29 publications
4
60
0
Order By: Relevance
“…TIS21 /BTG2/PC3 , a transcriptional co-regulator, interacts with CAF1 protein (Rouault et al 1998;Prevot et al 2001) and works as a coactivator of ERa-mediated transcription with CCR4 and hCAF1 (Morel et al 2003), and reviewed by Duriez et al (2004). The role of TIS21 /BTG2/PC3 for neurite outgrowth of PC12 cells (Rouault et al 1996;Cortes et al 2000;Guardavaccaro et al 2000;Tirone 2001) and its importance for differentiation of neuronal stem cells have extensively been studied in mouse ventricular epithelium (Calegari et al 2002(Calegari et al , 2005Canzoniere et al 2004;Corrente et al 2002;el-Ghissassi et al 2002;Iacopetti et al 1999;Kosodo et al 2004;Haubensak et al 2004). Recently, the regulatory role of TIS21 /BTG2/PC3 in stage-specific expansion of thymocyte (Konrad and Zuniga-Pflucker 2005) and its role as a negative regulator in hematopoietic progenitor expansion (Oswald et al 2005) have also been reported.…”
Section: Potential Roles Of Tis21 /Btg2/pc3mentioning
confidence: 99%
“…TIS21 /BTG2/PC3 , a transcriptional co-regulator, interacts with CAF1 protein (Rouault et al 1998;Prevot et al 2001) and works as a coactivator of ERa-mediated transcription with CCR4 and hCAF1 (Morel et al 2003), and reviewed by Duriez et al (2004). The role of TIS21 /BTG2/PC3 for neurite outgrowth of PC12 cells (Rouault et al 1996;Cortes et al 2000;Guardavaccaro et al 2000;Tirone 2001) and its importance for differentiation of neuronal stem cells have extensively been studied in mouse ventricular epithelium (Calegari et al 2002(Calegari et al , 2005Canzoniere et al 2004;Corrente et al 2002;el-Ghissassi et al 2002;Iacopetti et al 1999;Kosodo et al 2004;Haubensak et al 2004). Recently, the regulatory role of TIS21 /BTG2/PC3 in stage-specific expansion of thymocyte (Konrad and Zuniga-Pflucker 2005) and its role as a negative regulator in hematopoietic progenitor expansion (Oswald et al 2005) have also been reported.…”
Section: Potential Roles Of Tis21 /Btg2/pc3mentioning
confidence: 99%
“…PC3 mRNA is expressed in the neuroblast of the ventricular zone of the neural tube during the last proliferative cycle before differentiation into a postmitotic neuron and is therefore a marker for the birth of the neuron (Bradbury et al, 1991;Iacopetti et al, 1994Iacopetti et al, , 1999. Moreover, the ability of PC3 to induce cell cycle arrest in G 1 by inhibiting the transcription of cyclin D1, as was observed in fibroblasts (Guardavaccaro et al, 2000), and to potentiate the NGFmediated neuronal differentiation of pheochromocytoma cells (Corrente et al, 2002;el-Ghissassi et al, 2002) suggested that PC3 could act as a switch from proliferative to neuron-generating cell fate. To test this hypothesis, we produced two transgenic mouse models conditionally overexpressing PC3 in neuroepithelia.…”
Section: Introductionmentioning
confidence: 99%
“…Rather, PC3 strongly enhanced the NGFinduced differentiation of these cells (Corrente et al, 2002;el-Ghissassi et al, 2002;F. Tirone, unpublished data).…”
Section: Pc3-dependent Induction Of Math1 and Cell Cycle Arrest Are Cmentioning
confidence: 99%
“…Arginine Methylation and Cancer?-A number of studies have provided evidence linking arginine methylation with antiproliferative signaling or with a protective role against cancer (13,17,(65)(66)(67)(68)(69)(70)(71)(72). However, these observations may not be applicable to all PRMTs and all cancer types.…”
Section: Complex Genomic Structure At the 5ј-end Of The Prmt1 Gene Lementioning
confidence: 99%